2020
DOI: 10.1200/po.19.00298
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of BRAF V600E Pediatric Gliomas Treated With Targeted BRAF Inhibition

Abstract: PURPOSE Children with pediatric gliomas harboring a BRAF V600E mutation have poor outcomes with current chemoradiotherapy strategies. Our aim was to study the role of targeted BRAF inhibition in these tumors. PATIENTS AND METHODS We collected clinical, imaging, molecular, and outcome information from patients with BRAF V600E–mutated glioma treated with BRAF inhibition across 29 centers from multiple countries. RESULTS Sixty-seven patients were treated with BRAF inhibition (pediatric low-grade gliomas [PLGGs], … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 36 publications
1
100
0
1
Order By: Relevance
“…6,9,[43][44][45] It is difficult to make comparative statements regarding other targeted agents like selumetinib and trametinib, however, for whom the early data are descriptive in terms of sustained PRs or includes combined cohorts of low-grade patients treated with different BRAF/MEK inhibitors. [46][47][48] In conclusion, everolimus does demonstrate activity in pediatric patients with radiographically progressive LGGs and provides another potential option for patients with recurrent disease. Its limited, reversible toxicity and administration as a pill or liquid preparation obviates the need for intravenous access.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…6,9,[43][44][45] It is difficult to make comparative statements regarding other targeted agents like selumetinib and trametinib, however, for whom the early data are descriptive in terms of sustained PRs or includes combined cohorts of low-grade patients treated with different BRAF/MEK inhibitors. [46][47][48] In conclusion, everolimus does demonstrate activity in pediatric patients with radiographically progressive LGGs and provides another potential option for patients with recurrent disease. Its limited, reversible toxicity and administration as a pill or liquid preparation obviates the need for intravenous access.…”
Section: Discussionmentioning
confidence: 88%
“…Taking into consideration the 5‐year OS and PFS, this drug compares similarly to other standard chemotherapy trials for refractory disease utilizing vinblastine or upfront trials utilizing carboplatin/vincristine 6,9,43–45 . It is difficult to make comparative statements regarding other targeted agents like selumetinib and trametinib, however, for whom the early data are descriptive in terms of sustained PRs or includes combined cohorts of low‐grade patients treated with different BRAF/MEK inhibitors 46–48 …”
Section: Discussionmentioning
confidence: 99%
“…2,3 Response rates are promising and appear to be superior to those observed with chemotherapy. 4 However, little is known regarding the management of patients who fail to respond or progress while treated with MEK or BRAF inhibitors. We describe a patient with BRAF V600E mutated PLGG who progressed on a combination of dabrafenib and tramatenib, and eventually responded to thioguanine, procarbazine, lomustine, and vincristine (TPCV) resulting in reversal of life-threatening symptoms.…”
Section: Salvage Chemotherapy After Failure Of Targeted Therapy In a mentioning
confidence: 99%
“…Early trials have shown efficacy of BRAF and MEK inhibitors in recurrent/refractory PLGG 2,3 . Response rates are promising and appear to be superior to those observed with chemotherapy 4 . However, little is known regarding the management of patients who fail to respond or progress while treated with MEK or BRAF inhibitors.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation